2021
DOI: 10.3233/jpd-212624
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GBA and LRRK2 Are Not Associated with Increased Inflammatory Markers

Abstract: Background: Inflammation is an integral part of neurodegeneration including in Parkinson’s disease (PD). Ashkenazi Jews have high rates of genetic PD with divergent phenotypes among GBA-PD and LRRK2-PD. The role of inflammation in the prodromal phase of PD and the association with disease phenotype has yet to be elucidated. Objective: To assess central and peripheral cytokines among PD patients with mutations in the LRRK2 and GBA genes and among non-manifesting carriers (NMC) of these mutations in order to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…In a subgroup with CSF available, higher levels of S190 M. Zimmermann and K. Brockmann / Blood and Cerebrospinal Fluid Biomarkers of Inflammation in Parkinson's Disease VEGF and IL-8 were detected in PD patients with LRRK2 mutations compared to those with LRRK2wildtype status [66]. A recent study from Israel confirmed the findings of relatively similar inflammatory profiles between PD patients with vs. without LRRK2 mutations as the colleagues also did not find any differences in blood or CSF levels of cytokines [67].…”
Section: Genetic-associated Pd Lrrk2 (Leucine-rich Repeat Kinase 2)mentioning
confidence: 77%
See 1 more Smart Citation
“…In a subgroup with CSF available, higher levels of S190 M. Zimmermann and K. Brockmann / Blood and Cerebrospinal Fluid Biomarkers of Inflammation in Parkinson's Disease VEGF and IL-8 were detected in PD patients with LRRK2 mutations compared to those with LRRK2wildtype status [66]. A recent study from Israel confirmed the findings of relatively similar inflammatory profiles between PD patients with vs. without LRRK2 mutations as the colleagues also did not find any differences in blood or CSF levels of cytokines [67].…”
Section: Genetic-associated Pd Lrrk2 (Leucine-rich Repeat Kinase 2)mentioning
confidence: 77%
“…While 1 of the 3 studies reports higher serum levels of IL-1␤ [66], the other 2 studies did not find differences in inflammatory profiles in blood and/or CSF between non-manifesting LRRK2 mutation carriers and healthy controls, even when clinically stratified for prodromal markers [38,67]. A recent study in Norwegian individuals revealed higher CSF levels of TNF-␣ in LRRK2 mutation carriers when compared to controls [68].…”
Section: Genetic-associated Pd Lrrk2 (Leucine-rich Repeat Kinase 2)mentioning
confidence: 97%
“…And numerous studies suggest a role for LRRK2 in the immune function and microglial activation [87]. However, most of the studies addressing non-manifesting LRRK2 have found none or few changes in immune biomarkers in blood [70,88]. Brockmann et al showed no differences between non-manifesting LRRK2 and controls, although in manifested LRRK2-PD and iPD certain inflammatory markers differed suggesting a differential immune response in these two PD types [88].…”
Section: Peripheral Immune Changes In Probable Prodromal Pdmentioning
confidence: 99%
“…Hence, investigating the mechanisms and mediators through which GBA mutations initiate and propagate neuroinflammation is now a hot area of research [ 66 ]. Despite the mentioned association of GBA mutations with central and peripheral inflammatory responses, initial investigations of central and peripheral inflammatory cytokines as early markers of PD have returned with negative outcomes [ 67 ].…”
Section: The Role Of Monogenic Parkinson’s Disease Known Genes In The...mentioning
confidence: 99%